Upasakajanalankara : a critical edition and study - Pali Text Society; Saddhatissa, H. (London : Pali Text Society, 1965)
Commentary on the Buddhist canonical work.
Microfiche.
Keywords: Tripitaka. -- Commentaries; Buddhist monasticism and religious orders -- Rules